School principals and democratic management in the ABC paulista region - Garcia, Paulo Sérgio; Prearo, Leandro Campi; Romero, Maria do Carmo; Bassi, Marcos Sidnei (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2016)
Brazil faces the challenge of promoting quality in public schools and in the process, among many things, the principal plays an important role. This is a professional who influence the school and student achievements through his profile and democratic management. This study aims to identify and analyze the characteristics of school principals of the metropolitan area of São Paulo (Região do Grande ABC Paulista) and, in parallel, to investigate how the democratic management processes have been conducted in public schools in the same region. A case study was used to collect information, initially from School Census 2013 on principal profile, and on democratic management. These findings were contextualized using interviews with school principals (N=26). The results showed that the majority of principals are women, above 40 years old, majored in pedagogy, in private institutions, in traditional courses, with experience of more than five years. Regarding the democratic school management, it was found that it is still a fragile process that is much more concrete in the principals’ discourse than in their daily practices. Democratic management has been much more an inspiring symbol than a mechanism to encourage daily action. These results can be used to foster discussions between specialists in education and school principals as well as in the principal pre-service education.